Readings for diversity and social justice - Adams, Maurianne, 1938-; Blumenfeld, Warren J., 1947-; Castañeda, Carmelita Rosie, 1960-; Hackman, Heather; Peters, Madeline L.; Zúñiga, Ximena (Routledge, Taylor & Francis Group, 2013)
"Readings for Diversity and Social Justice is the market leading anthology to cover the full scope of social oppression from a social justice standpoint. With full sections dedicated to racism, sexism, classism, heterosexism, and ableism, as well as transgenderism, ethno-religious oppression, and adult and ageism, this bestselling text goes far beyond the range of traditional readers. New essay selections in each section have been carefully chosen to keep topic coverage timely and readings accessible and engaging for students. The interactions among these topics are highlighted throughout to stress the interconnections among oppressions in everyday life.Each thematic section is divided into three parts: Contexts, Personal Voices, and Next Steps and Actions. The first two parts provide vivid portraits of the meaning of diversity and the realities of oppression. The third part challenges the reader to take action to end oppressive behavior and affirm diversity and social justice. Retaining the key features and organization that has made Readings for Diversity and Social Justice an indispensable text for teaching issues of social justice while simultaneously updating and expanding its coverage, this new edition features:Strong and accessible section introductions to highlight key points and relate the essential concepts of any given topic to other forms of oppression. Updated sections to include new accessible, engaging and poignant selections that maximize student engagement. Contextual pieces to theorize structural inequality; personal narratives to provide vivid portraits of "difference" and "otherness"; and next steps to challenge the reader to take action. An emphasis on the interconnectedness of social identity and social inequality throughout.An alternative, thematic table of contents.An updated companion website with additional resources, including videos, further suggested readings, and teaching materials"--Resumé vydavatele